Význam endoskopické retrográdní cholangiopankreatografie v diagnostice poranĕní pankreatu u dĕtí - Koudelka, J; Králová, M; Preis, J; Dítĕ, P; Vacek, Z (Rozhledy v chirurgii, 1991)
The condition of the main pancreatic duct determines very probably in a decisive way the fate of posttraumatic pancreatic pseudocysts and acute pancreatic injuries. Endoscopic retrograde cholangiopancreatography is the only diagnostic method which makes possible to evaluate the condition of this duct. The authors performed ERCP in three children, in two of them an internal drainage of the pseudocyst was carried out on account of verified ductal rupture. In the third girl, after evidence of an intact main pancreatic duct, conservative therapy was successfully applied. In the discussion the authors summarize data from the literature regarding the use of ERCP in the preoperative diagnosis of posttraumatic pancreatic pseudocysts and acute pancreatic injuries. The authors consider ERCP a method which renders the diagnosis of posttraumatic pancreatic pseudocysts and acute pancreatic injuries more accurate.
Keywords: pankreatická pseudocysta; Wounds and Injuries; Pancreas; rány a poranění; mužské pohlaví; Pancreatic Pseudocyst; ženské pohlaví; Cholangiopancreatography, Endoscopic Retrograde; Humans; Adolescent; Female; pankreas; Child; dítě; lidé; Male; mladiství; cholangiopankreatografie endoskopická retrográdní